36.0k views
4 votes
Need help ASAP please fellas!

Need help ASAP please fellas!-example-1
User PromInc
by
4.9k points

2 Answers

3 votes
Use BEMDAS:
Brackets, Exponents, Multiplication and Division, Addition and Subtraction

1.2+0.8:4-3\cdot(0.7-0.81)=1.2+0.2-3\cdot(-0.11)=1.2+0.2+0.33=1.73


User Didier Malenfant
by
6.1k points
4 votes
The answer to this question is 1.73
1.2 + 0.8 ÷ 4 - 3(0.7 - 0.81)
= 1.2 + 0.8 ÷ 4 - 3(-0.11)
= 1.2 + 0.2 - 3(-0.11)
= 1.2 + 0.2 + 0.33
= 1.73
User Atousa Darabi
by
5.6k points